2012
DOI: 10.1007/s12560-012-9091-z
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Known and Hypothetical Transmission Routes for Noroviruses

Abstract: Human noroviruses (NoVs) are considered a worldwide leading cause of acute non-bacterial gastroenteritis. Due to a combination of prolonged shedding of high virus levels in feces, virus particle shedding during asymptomatic infections, and a high environmental persistence, NoVs are easily transmitted pathogens. Norovirus (NoV) outbreaks have often been reported and tend to affect a lot of people. NoV is spread via feces and vomit, but this NoV spread can occur through several transmission routes. While person-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 206 publications
1
65
0
1
Order By: Relevance
“…Swine illnesses are associated with porcine Sapovirus while the influence of Norovirus contagions in swine is unknown [3]. Some strains of Caliciviruses (Norovirus and Sapovirus) have the potential for zoonotic transmission since they are hereditarily related to humans [13] and studies have shown that some domestic pigs serve as the reservoir of these viruses [14].…”
Section: Introductionmentioning
confidence: 99%
“…Swine illnesses are associated with porcine Sapovirus while the influence of Norovirus contagions in swine is unknown [3]. Some strains of Caliciviruses (Norovirus and Sapovirus) have the potential for zoonotic transmission since they are hereditarily related to humans [13] and studies have shown that some domestic pigs serve as the reservoir of these viruses [14].…”
Section: Introductionmentioning
confidence: 99%
“…The primary transmission route is the faecal-oral one, either via person-to-person contact or by consumption of contaminated food or water (Lopman et al 2003;Siebenga et al 2007;Kroneman et al 2008;Scallan et al 2011;Mathijs et al 2012). Noroviruses are very resistant and can persist for several days in the environment (D'Souza et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Noroviruses are very resistant and can persist for several days in the environment (D'Souza et al 2006). Due to this high persistence on various inanimate surfaces and on food, coupled with the prolonged shedding of high amounts of virus in faeces and the low infectious dose, person-to-person transmission is very efficient and noroviruses constitute a serious public health issue (Mathijs et al 2012). Alternatively, food can be contaminated with HuNoV either at the source in the growing or harvesting areas by contaminated irrigation water or during handling or preparation of meals (Tuan Zainazor et al 2010;Mathijs et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Produce safety is of great concern as fresh produce serves as the major vehicle for huNoV transmission (8,9). Produce that is consumed raw or with little or no processing may become contaminated with huNoV during postharvest handling (e.g., irrigation water and amendments) and processing (e.g., washing and packing) and also through contact with infected individuals who may handle the produce or seeds (10)(11)(12). Previously, huNoV has been detected in surface water and groundwater with various frequencies (13,14).…”
mentioning
confidence: 99%
“…Previously, huNoV has been detected in surface water and groundwater with various frequencies (13,14). It is likely that viruses can be spread by water, and internalization of huNoV through root uptake of produce via polluted irrigation water is one of the potential routes for plant contamination (12,14). However, without an appropriate cell culture model, the behavior of huNoV is still not well understood.…”
mentioning
confidence: 99%